Melville’s Obsessional Form: Disjunction and Refusal in “Benito Cereno” - Matthew Scully (European Journal of American Studies)
“Benito Cereno” offers an exemplary text to consider obsession in relation to narrative form. Melville’s tale operates on at least two levels: the first part, a third-person narration that exhausts itself when “Melville’s ultimate dupe” (Ngai 61), Captain Delano, finally realizes there has been a slave revolt on Cereno’s ship, and the second part, transcripts from legal depositions in the court case that makes a sovereign judgment on Babo and the events of the preceding narrative. Yet this judgment does little to resolve the narrative’s tensions. Drawing on psychoanalytic theory, I argue for obsession as the governing formal principle of Melville’s narrative. The necessary and yet impossible coincidence of multiple levels of narration that characterizes obsession offers a compelling way to reread Melville’s representation and critique of the anti-Black fantasies that organize the society displayed in the story. The perpetual turning motion constitutive of obsessional form thus helps redescribe the competing narrative styles of “Benito Cereno,” as well as the aesthetic and political implications of Babo’s resistance to the anti-Black structures of Delano and Cereno’s world. Reading “Benito Cereno” in terms of obsessional form reveals its profound critique of anti-Blackness and the anti-Black fantasies sustaining it.